Spindle Cell Lipoma of the Buccal Mucosa- A Case Report - Mary Mathew; Monica Charlotte Solomon (Cumhuriyet Dental Journal, 2019)
Spindle cell lipomas are a distinct variant of lipomas that occur very rarely in the oral cavity. The most common site for occurrence of this entity in the oral cavity is the tongue. The presence of spindle cells in the lesion calls for critical histopathological evaluation of the lesion. Here we present a new case of spindle cell lipoma that occurred on the buccal mucosa of a 45-year-old female patient. We provide an insight to the pathogenesis and the pathology of the entity.